Kinematic tomography of oscillatory coherent structures through synchronized mode decomposition - Silin, Nicolas; Boroni, Gustavo Adolfo; Higham, J. E.; Clausse, Alejandro (IOS Press, 2022)
Fil: Silin, Nicolas. Universidad Nacional de Cuyo; Argentina. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina